Parity Reversion in Real Exchange Rates : Fast, Slow or Not At All? - McDermott, C. (IMF Working Papers; Working Paper ;, 2004)
Consensus estimates put the half-life of deviations from purchasing power parity (PPP) at about four years (Rogoff, 1996). However, conventional least squares estimates of half-lives are biased downward. Accordingly, as a preferred measure of the persistence of real exchange rate shocks, this study uses median-unbiased estimators of the half-life of deviations from parity, which correct for the downward bias of conventional estimators. The paper tests for PPP using real effective exchange rate data for 90 developed and developing countries in the post-Bretton Woods period. Support for PPP is found, as the majority of countries experience finite deviations of real exchange rates from parity. The speed of parity reversion is found to be typically much faster for developed countries than for developing countries, and to be considerably faster for countries with flexible nominal exchange rate regimes in comparison with countries having fixed nominal exchange rate regimes.